Performance analysis of supercritical carbon dioxide-brayton cycle for waste heat recovery using aspen plus - Chong, Zhi Ken; Saadon, Syamimi (Akademia Baru Publishing, 2022)
This study will focus on technologies and applications that has excelled in other industries, but yet to be explored in aviation, which is waste heat recovery technology, with supercritical carbon dioxide as the cycle’s working fluid, in reducing jet engines’ fuel consumption and minimizing fuel expenses and carbon dioxide emissions. Research on the analysis of a cycle thermodynamically to be integrated into a turbofan jet engine will be highlighted in this paper. The analysis will be conducted via simulation within the Aspen Plus software and result’s post-processing via Microsoft Excel. A quantitative analysis to select the best performing cycle configuration, as well as the jet engine’s performance increment after the cycle’s integration as its waste heat recovery system, are presented in this paper. The results stated that for both thermal efficiency and net work, recuperation cycle (42.46 %, 2197.67 kW) performs much better than basic Brayton cycle (18.53 %, 2555.84 kW).